2008
DOI: 10.1634/theoncologist.2007-0207
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab plus Paclitaxel or Docetaxel in HER-2–Negative/HER-2 ECD–Positive Anthracycline- and Taxane-Refractory Advanced Breast Cancer

Abstract: Trastuzumab is considered effective against human epidermal growth factor receptor (HER)-2-positive breast cancer as assessed by immunohistochemistry (IHC) and fluorescence or chromogenic in situ hybridization (FISH/ CISH) on biopsy material. Trastuzumab is now approved in both the adjuvant and metastatic settings for this patient population. Because HER-2 extracellular domain (ECD) levels have been correlated with disease progression in the metastatic setting, we considered trastuzumab salvage therapy plus a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…In our experiment, some cases with negative tissue HER2 also showed high serum HER2 ECD concentrations. Ardavanis et al found that the HER2 tissue negative but serum positive patients can be benefited from trastuzumab therapy [23]. Thus, a potential utility of serum HER2 ECD is to identify patients who missed the opportunity of being treated with HER2-targeted therapies due to a lack of overexpression of HER2 in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, some cases with negative tissue HER2 also showed high serum HER2 ECD concentrations. Ardavanis et al found that the HER2 tissue negative but serum positive patients can be benefited from trastuzumab therapy [23]. Thus, a potential utility of serum HER2 ECD is to identify patients who missed the opportunity of being treated with HER2-targeted therapies due to a lack of overexpression of HER2 in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab, a humanized monoclonal antibody that targets human epidermal growth factor receptor 2 (HER2), is routinely used to treat patients with breast carcinoma who overexpress HER2 [2,3]; when combined with chemotherapy in the metastatic setting, trastuzumab improves progression-free survival and overall survival by years [4]. Other HER2-targeting drugs (e.g., the kinase inhibitor lapatinib [5], the antibody pertuzumab [6], the antibody-drug conjugate adotrastuzumab emtansine [T-DM1] [7]) have been approved for use in the treatment of HER2-positive metastatic breast cancer. At the same time, it has been shown that lapatinib (when added to paclitaxel) [8] and pertuzumab (as a single agent) [9] offer no clinical benefit to patients with HER2-negative metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…15 Indeed, 16 of 22 HER-2-negative patients with an HER-2 extracellular domain level >15ng/mL showed a clinical benefit, which led to the concept of "hidden" HER-2-positive breast cancer. 16 Furthermore, contrary to expectations, the level of HER-2 did not predict clinical response and showed a U-shaped relationship, which suggested that trastuzumab could be effective in HER-2-negative tumors. 17 Another example is cetuximab, the anti-epidermal growth factor receptor (EGFR) drug, originally studied only in patients with EGFR-expressing tumors until it was found to be beneficial for some patients with EGFR negative tumors as well.…”
Section: Original Research Articlementioning
confidence: 64%